Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1017/s0954102011000824
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial diversity for an anthropogenic impact assessment in the Sør Rondane Mountains area, Antarctica

Abstract: Abstract:The recently inaugurated Belgian Princess Elisabeth Station has been built in the Sør Rondane Mountains (Dronning Maud Land). The construction site is situated close to the Utsteinen Nunatak (71857'S, 23820'E), on a granite ridge. Prior to the survey and construction activities, the site had been subject to limited or no direct human impacts. Therefore, a biological inventory has been started for future evaluations of human impacts in the area. This study presents the cyanobacterial diversity of ten s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…The samples were analyzed by DGGE based on the V3 and V4 region of the 16S rRNA as described by Fernandez-Carazo et al (2012), and the DGGE gels were duplicated for reproducibility. We used two sets of primers 16S378F/16S781RaGC and 16S378F/16S781RbGC as described by Boutte et al (2006).…”
Section: Cyanobacterial Diversity Studied Using Dggementioning
confidence: 99%
See 1 more Smart Citation
“…The samples were analyzed by DGGE based on the V3 and V4 region of the 16S rRNA as described by Fernandez-Carazo et al (2012), and the DGGE gels were duplicated for reproducibility. We used two sets of primers 16S378F/16S781RaGC and 16S378F/16S781RbGC as described by Boutte et al (2006).…”
Section: Cyanobacterial Diversity Studied Using Dggementioning
confidence: 99%
“…For example, in the Sør Rondane Mountains, a cultivation-based study of bacteria in two samples revealed the presence of five major phyla, namely Actinobacteria, Bacteroidetes, Proteobacteria, Firmicutes and Deinococcus-Thermus, covering 35 different genera, which included a considerable number of potentially new species and genera distributed over 24 genera belonging to different phylogenetic groups (Peeters, Ertz and Willems 2011). Denaturing Gradient Gel Electrophoresis (DGGE) and microscopy of the cyanobacterial community structure in 10 samples taken in the vicinity of the construction site of the Princess Elisabeth station before it was built revealed the presence of 10 morphotypes and 13 Operational Taxonomic Units (OTUs) belonging to the Oscillatoriales, Chroococcales, Nostocales and Stigonematales (Fernandez-Carazo et al 2012); 46% of the OTUs appeared to be restricted to Antarctica. For microeukaryotes, biodiversity data are still largely lacking for these regions.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed molecular diversity of cyanobacteria in Antarctic terrestrial communities of the Sør Ron dane Mountains and carried out bioinformatic analy sis of cyanobacterial diversity throughout the conti nent [15,16]. Antarctic cyanobacteria were shown to exhibit high diversity.…”
Section: Mountain Peaks Above the Ice Sheet Surfacementioning
confidence: 99%
“…Terrestrial Antarctica represents one of the most extreme environments a living organism can thrive in (1, 2). Precipitation is limited (3), and of this, the majority falls as snow and ice crystals that do not melt but build up over time to form massive ice sheets.…”
Section: Introductionmentioning
confidence: 99%
“…The high elevation together with reflection of sunlight by the snow and ice cover, not allowing heat energy absorption, contribute to the low temperatures reaching −89 °C once in 1983 (4, 5). Antarctica experiences total darkness during winter, while during summer, it receives 24-hour-sunlight, and with this, damaging UVB rays (1, 6). The harsh environmental conditions of Antarctica have consequently shaped the simple trophic structures present in Antarctic soil ecosystems (7).…”
Section: Introductionmentioning
confidence: 99%